Genome-wide data reveal cryptic diversity and genetic introgression in an Oriental cynopterine fruit bat radiation - Chattopadhyay, Balaji (BMC Evol Biol, 2016)
BACKGROUND: The Oriental fruit bat genus Cynopterus, with several geographically overlapping species, presents an interesting case study to evaluate the evolutionary significance of coexistence versus isolation. We examined the morphological and genetic variability of congeneric fruit bats Cynopterus sphinx and C. brachyotis using 405 samples from two natural contact zones and 17 allopatric locations in the Indian subcontinent; and investigated the population differentiation patterns, evolutionary history, and the possibility of cryptic diversity in this species pair. RESULTS: Analysis of microsatellites, cytochrome b gene sequences, and restriction digestion based genome-wide data revealed that C. sphinx and C. brachyotis do not hybridize in contact zones. However, cytochrome b gene sequences and genome-wide SNP data helped uncover a cryptic, hitherto unrecognized cynopterine lineage in northeastern India coexisting with C. sphinx. Further analyses of shared variation of SNPs using Patterson’s D statistics suggest introgression between this lineage and C. sphinx. Multivariate analyses of morphology using genetically classified grouping confirmed substantial morphological overlap between C. sphinx and C. brachyotis, specifically in the high elevation contact zones in southern India. CONCLUSION: Our results uncover novel diversity and detect a pattern of genetic introgression in a cryptic radiation of bats, demonstrating the complicated nature of lineage diversification in this poorly understood taxonomic group. Our results highlight the importance of genome-wide data to study evolutionary processes of morphologically similar species pairs. Our approach represents a significant step forward in evolutionary research on young radiations of non-model species that may retain the ability of interspecific gene flow. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12862-016-0599-y) contains supplementary material, which is available to authorized users.